Pesticides and Herbicides. (1st October 2014) - Mahour, Reza; Khan, Muhammad Faizan; Forbes, Sara; Perez‐Estrada, Leonidas A.
Abstract : This is a review of literature published in 2013 related to the presence of pesticides and herbicides in the environment. The review, divided into four sections, includes toxicology, ecology, risk assessment, modelling and treatment strategies.